FASHAKH NIKAH DUE TO DEFECTS (‘AIB): ANALYSIS OF CRITERIA AND LEGAL IMPLICATIONS ACCORDING TO WAHBAH AZ-ZUHAILI - Berliano Arrasyid; Irfan Zulfikar; Muhammad Hafis; Mardiana (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study analyzes Wahbah Al-Zuhaili's views on defects (‘aib) as grounds for fasakh (annulment of marriage) and their relevance to the Compilation of Islamic Law (KHI). A literature review of Al-Fiqh al-Islami wa Adillatuhu reveals that Al-Zuhaili rejects limiting ‘aib to the traditional list. He innovatively develops two criteria: functional (defects that hinder the essential objectives of marriage, such as conjugal relations) and harmonization (defects that cause harm, revulsion, or destroy marital tranquility/sakinah). This maqasid-based approach implies an expansion of the right to khiyar al-‘aib and clarity in legal consequences, including the status of irrevocable divorce (talak bain), stipulations on dowry, and the possibility of compensation. In a contemporary context, this framework is relevant for accommodating modern chronic illnesses such as HIV/AIDS or severe mental disorders that undermine the foundation of marriage. A comparative analysis with the KHI reveals a principled alignment in Article 75, yet a procedural divergence: the KHI emphasizes formal court proceedings, whereas Al-Zuhaili prioritizes restorative justice. These findings recommend employing Al-Zuhaili's thought as an analytical lens for the progressive interpretation of the KHI, enabling Indonesian Islamic family law to be more responsive and equitable in resolving contemporary marital disputes arising from defects.